Trusting Records: Is Blockchain Technology the Answer?. (18th July 2016) - Lemieux, Victoria Louise
Abstract : Purpose: This paper seeks to explore the value of Blockchain technology as a solution to creating and preserving trustworthy digital records, presenting some of the limitations, risks and opportunities of the approach. Design/methodology/approach: The methodological approach involves using the requirements embedded in records management and digital preservation standards, specifically ISO 15489, ARMA's Generally Accepted Recordkeeping Principles, ISO 14721 and ISO 16363, as a general evaluative framework for a risk-based assessment of a specific proposed implementation of Blockchain technology for a land registry system in a developing country. Findings: The results of the analysis suggest that Blockchain technology can be used to address issues associated with information integrity in the present and near term, assuming proper security architecture and infrastructure management controls. It does not, however, guarantee reliability of information in the first place, and would have several limitations as a long-term solution for maintaining trustworthy digital records. Originality/value: This paper contributes an original analysis of the application of Blockchain technology for recordkeeping.